The will to live – breast cancer patients perceptions' of palliative chemotherapy. (2nd September 2017) - Bergqvist, Jenny; Strang, Peter
Abstract: Background: For women with metastatic breast cancer, late lines of chemotherapy might be beneficial but also harmful. Ongoing chemotherapy late in life increase the risk of late or absent discussions of palliative care and access to symptom relief by other options than chemotherapy. Our aim was, therefore, to investigate breast cancer patients' motives, perceptions, and experiences of late lines of palliative oncologic treatment. Material and methods: A qualitative study with semi-guided face-to-face interviews with 20 women on at least their second line of palliative chemotherapy (second–eighth line). All women had breast cancer and were 40–80 years old. The interviews were analyzed by a phenomenographical approach according to seven steps, which uses a second-order perspective, i.e., how the informants experience the world. Results: The categories that surrounded the decision to continue with palliative chemotherapy were: The decision, Personal motives and goals and The treatment. All women acknowledged that they knew they had incurable breast cancer and that the treatment goal was to slow down cancer growth. Fear of death was a strong motive for all women in addition to experience of new values of life, still they preferred the doctor to make the decision. Cancer symptoms, especially pain triggered death anxiety, whereas the patients patiently accepted similar side effects from the treatment. There were also external motives for treatment like wishes from family, friends, but also health care staff. Conclusions: All women knew they had disseminated breast cancer, still they expressed hopes for cure, therefore, death was more of a threat than a reality of an imminent death. None of the women had perceived there was an option to stop treatment. They felt both their families and doctors expected them to continue. Death threat was their main motive for accepting treatment.